Synchronisation of quantitative easing and fiscal expansion: Macroeconomic effects in times of crises - Mária Liptáková; Veronika Šuliková; Marianna Siničáková; Jana Budová (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2024)
The purpose of the paper is to capture macroeconomic responses of quantitative easing in times of financial and non-financial crisis and to confront the extent of the output responses with the synchronisation of quantitative easing and expansionary fiscal policy. Several methodological approaches have been implemented to achieve this aim. Firstly, bibliometric analysis of scientific papers in the field shows the existence of liaisons between quantitative easing and fiscal policy (government debt) in scientific research. Secondly, cross-correlations and Granger causality tests uncover the effects on GDP, industrial production, inflation, and nominal effective exchange rate in the US, the euro area, and the UK (during the period 2007 - 2022) and Japan (during the period 2000 - 2022). The macroeconomic effects of quantitative easing are the most important in the UK and Japan during the financial crisis and in the US during the non-financial crisis. The findings confirm the idea that quantitative easing has a generally higher causal effect on output (or industrial production) if it is accompanied and supported by fiscal expansion, i.e. after the pandemic (non-financial crisis). The scientific value of the paper is that it fills the gap in current research by demonstrating the macroeconomic effects of the pandemic quantitative easing in Japan and the UK and taking the results in the context of fiscal policy and quantitative easing synchronisation.
Keywords: E31; E51; E52; E58; E62; 330; Quantitative easing; Financial crisis; Non-financial crisis; Cross-correlations; Granger causality